C-Reactive Protein to Albumin Ratio: A Reliable Marker in Colorectal Cancer - Özlem Zeliha Sert; Hilmi Bozkurt; Tolga Ölmez; Emre Aray; Orhan Uzun; Selçuk Gülmez; Aziz Serkan Zenger; Erdal Polat; Mustafa Duman (Turkish Journal of Colorectal Disease, 2021)

(untitled)
Aim:Postoperative complications after colorectal cancer surgery result in increased treatment costs, prolonged hospital stays and poor prognosis and reduce quality of life of the patients. Here, we aim to contribute to the literature in terms of being a reliable marker of postoperative C-reactive protein (CRP) to albumin ratio (CAR) after colorectal cancer surgery.Method:A total of 213 patients undergoing colorectal cancer surgery between 2013 and 2018 were analyzed in this study. Risk factors for the development of postoperative complications were analyzed using univariate and multiple logistic regression models. A receiver operating characteristic (ROC) curve analysis was used to analyze the association with the CRP and CAR variables, with the aim being to differentiate postoperative complications.Results:Postoperative complications occurred in 87 (40.8%) patients. Based on the Clavien-Dindo classification, 25 (18.7%) patients developed major complications. Perioperative blood transfusion [odds ratio (OR)=1.3; 95% confidence interval (CI)=1.08-1.55] and postoperative CAR (OR=1.2; 95% CI=1.05-1.35) were independent risk factors for postoperative complications (p=0.005 for each). The cut-off value for CAR was 4.3 (sensitivity: 51.72; specificity: 71.43; and area under the curve: 0.642), meaning that CAR was found to be statistically significantly effective in differentiating postoperative complications (p<0.001). The (median) length of hospital stay was statistically significantly longer in the high CAR (>4.3) group (p=0.001), while the laparoscopic surgery rate was statistically significantly lower in the high CAR group (p=0.039).Conclusion:CAR is a novel, reliable and independent marker. Moreover the ratio is useful for clinicians and provides the determination of early postoperative complications after colorectal cancer surgery.